POS11 Blood markers and poor outcome after acute cerebrovascular disease: a prospective cohort study. Issue 11 (22nd October 2010) - Whiteley, W; Rumley, A; Sattar, N; Wardlaw, J M; Lowe, G D O; Welsh, P; Green, A; Sandercock, P A G; Dennis, M S
Abstract : Background: Biomarkers might add to clinical measures of neurological impairment and age to predict poor outcome after stroke. Methods: We recruited symptomatic patients <24 h after stroke or TIA from an emergency department. We drew blood for markers of inflammation, thrombosis, thrombolysis, cardiac dysfunction and cerebral damage. We measured outcome at 3 months with the modified Rankin Scale (mRS). We used logistic regression, calculated measures of discrimination and reclassification and adjusted for multiple comparisons. Results: We drew blood from 285 patients (230 ischaemic strokes, 40 TIA, 15 haemorrhagic strokes) at a median of 7 h (IQR 3–19 h) after symptom onset and contacted 99% at 3 months: 160 (57%) had mRS 0–2 and 123 (43%) had mRS 3–6. After adjusting for neurological impairment and age, only IL-6 (OR 2.4 (95% CI 1.4 to 4.2), 75th to 25th centile) and Ln NT pro BNP (OR 2.2 (1.2 to 4.0)) were significantly associated with poor outcome. A clinical model containing the NIHSS score and age had an area under a receiver operator curve of 0.84 (95% CI 0.79 to 0.88); neither IL-6 nor Ln NT pro-BNP improved this significantly. There was no net reclassification improvement across clinically important boundaries after adding IL-6 or Ln NT pro-BNP to the clinical model. Conclusion: It is unlikely that the biomarkers measured in this study improve the clinical prediction of death or disability when measured at a uniform and early point after stroke or TIA.